Prognostic Biomarker DDOST and Its Correlation With Immune Infiltrates in Hepatocellular Carcinoma - Zhu, Changyu; Xiao, Hua; Jiang, Xiaolei; Tong, Rongsheng; Guan, Jianmei (Frontiers in Genetics, 2022)
Background: Dolichyl-Diphosphooligosaccharide --Protein Glycosyltransferase Non-Catalytic Subunit (DDOST) is an important enzyme in the process of high-mannose oligosaccharide transferring in cells. Increasing DDOST expression is associated with the impairing liver function and the increasing of hepatic fibrosis degrees, hence exacerbating the liver injury. However, the relation between DDOST and hepatocellular carcinoma (HCC) has not been revealed yet. Method: In this study, we evaluated the prognostic value of DDOST in HCC based on data from The Cancer Genome Atlas (TCGA) database. The relationship between DDOST expression and clinical-pathologic features was evaluated by logistic regression, Wilcoxon signed-rank test, and Kruskal-Wallis test. Prognosis-related factors of HCC including DDOST were evaluated by univariate and multivariate Cox regression and the Kaplan-Meier (KM) method. DDOST-related key pathways were identified by gene set enrichment analysis (GSEA). The correlations between DDOST and cancer immune infiltrates were investigated by single-sample Gene Set Enrichment Analysis (ssGSEA) of TCGA data. Results: High DDOST expression was associated with poorer overall survival (OS) and disease-specific survival (DSS) of HCC patients. GSEA suggested that DDOST regulates is closely correlated with cell cycle and immune response via the PPAR signaling pathway. ssGSEA indicated that DDOST expression was positively correlated with infiltrating levels of Th2 cells and negatively correlated with infiltrating levels of Cytotoxic cells. Conclusions: All those findings indicated that DDOST was correlated with prognosis and immune infiltrating in HCC.